Estudio de las tensiones en válvulas biplanas tipo mariposa - Manescu, Tiberiu; Bocîi, Liviu Sebastian; Copaci, Ion; Pinca-Bretotean, Camelia (Revista Facultad de Ingeniería Universidad de Antioquia, 2003)
This paper presents the study of tensions developed as a result of the static actuation developed in a biplane valve, butterfly type, with a 1.500 mm diameter, loaded with a pressure of 1 MPa, using the finite element method, experimentally verified using a resistive electrical tensiometrical method. The proper knowledge of those valve types is very important in order to control the admissible losses.